2020
DOI: 10.17222/mit.2019.129
|View full text |Cite
|
Sign up to set email alerts
|

Improving the crosslink density and the mechanical properties after vulcanization for an iron oxide layer (scale) and SBR/rubber masterbatch

Abstract: In this study iron oxide layers (IOLs) formed on the surfaces of ingots during a rolling process were supplemented into stiren-butadiene rubber (SBR) based on a referenced rubber-back composition of 5-10-15-20 %, and accordingly five different samples were prepared. After vulcanization, the hardness, density, abrasion loss, tensile strength, percentage elongation, tearing strength and crosslink densities were measured. In addition to that, the effects of the crosslink density on the mechanical properties are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The mechanical properties of rubber compounds depend on many factors, for example , the chemical structure of the rubber matrix, the type and ratio of the fillers, the amount and type of cross-linker, the degree of crosslinking, the dispersion of cross-linkers, and the vulcanization conditions. 25 In this study, the mechanical properties in the presence of PNCA were evaluated by associating them with crosslink density.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical properties of rubber compounds depend on many factors, for example , the chemical structure of the rubber matrix, the type and ratio of the fillers, the amount and type of cross-linker, the degree of crosslinking, the dispersion of cross-linkers, and the vulcanization conditions. 25 In this study, the mechanical properties in the presence of PNCA were evaluated by associating them with crosslink density.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the iron oxide layer drastically reduced the cost of the pulp, caused an increase in wear resistance with an increased crosslink density, and provided advantages in some of the mechanical properties. 25…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation makes it important to carefully select the filler used and to conduct additional studies to improve the properties of the fillers. 9,10 Carbon black obtained from fossil fuel sources is commonly used as a filling material in rubber production. With carbon black, both the production cost is reduced and the mechanical properties are improved.…”
Section: Introductionmentioning
confidence: 99%
“…Bu nedenle kauçuk endüstrisinde birçok organik ve inorganik malzemenin dolgu malzemesi olarak kullanılmasının önemli olduğunu vurgulayan çalışmalar vardır [20]. Birçok bilim insanı yaptığı çalışmalarda, tarımsal ve endüstriyel atıklarının geri dönüşümünün önemli olduğunu rapor etmişlerdir [21][22][23][24][25].…”
Section: Gi̇ri̇ş (Introduction)unclassified